Would internalisation of external costs change cost-competitiveness of different energy sources? - Matevž Obrecht (Journal of Contemporary Economic and Business Issues, 2014)
The world currently stands witness to increasing energy demand mainly because of population growth and improvements in the standard of living. This causes highly negative environmental constraints since energy production, especially from conventional energy sources, is a very intense polluter. Therefore, any new energy infrastructure, especially new energy production facilities, must be carefully planned and designed and their cost competitiveness must be studied in details. Along with more traditional studies, considering mainly investment and production costs, external costs must be taken into account when making a feasibility study of a new power plant on a new country energy mix. Consideration of external costs is also crucial for efficient long term re-evaluation of different energy sources and technologies used in energy industry. The internalisation of external costs shows us the way to evaluate energy systems with inclusion of all environmental and social costs generated in the energy industry. In this paper we attempt to show which renewable energy sources are competitive with conventional energy sources if we internalize external costs. The study is made on the basis of external costs data for the European States which are interesting for the States of former Yugoslavia as well. The results have shown that competitiveness of renewables would change dramatically if all costs are taken into account.
Keywords: Q58; Q52; Q42; 330; external costs; production costs; renewables; Europe; polluter pays principle